ANALISIS PENGGUNAAN PUPPET PIN RIGGING PADA PERGERAKAN KARAKTER ANIMASI 2D - Dhimas Adi Satria (JURNAL ILMIAH INFORMATIKA, 2019)
Making animation at this time is already uses digital media using software or applications, many new techniques that emerge in making these animations whose function makes it easy for animation makers (animators). Especially for 2D animation is usually made manually or drawn one by one or the term frame by frame with celulloid media or digital drawing stacked together to move the object of animation. Puppet Pin is one of the tools available in Adobe After Effect. Utilizing Puppet Pin as Rigging on character movements will create convenience in 2D animation movements. This study aims to determine the type and making of suitable characters so that it is easy to apply into the Puppet Pin Rigging technique so that it can improve time efficiency, the number of characters to be drawn, and also the efficiency of the many movements that can be utilized in one character compared to frame by frame manually